2021
DOI: 10.3390/rs13081474
|View full text |Cite
|
Sign up to set email alerts
|

GPR Monitoring of Artificial Debonded Pavement Structures throughout Its Life Cycle during Accelerated Pavement Testing

Abstract: The paper gives an overview of a ground penetrating radar (GPR) experiment to survey debonding areas within pavement structure during accelerated pavement tests (APT) conducted on the university Gustave Eiffel’s fatigue carrousel. Thirteen artificial defect sections composed of three types of defects (Tack-free, Geotextile, and Sand-based) were embedded during the construction phase between the top and the base layers. The data were collected in two stages covering the entire life cycle of the pavement structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The ratio values are calculated based on the angles (θ 1 , θ 2 ) corresponding to the maximum point inside the box. The estimated permittivity values of asphalt over the three zones, as indicated in Table 5, fall within the commonly encountered range for road asphalt [33][34][35] and are consistent with results reported in [27] over the same test circuit. The similar ε r 's of asphalt over the sand and air-gap zones are estimated from measurements acquired during the same sunny day, whereas over the geotextile zone, the measurement took place after a rain event, resulting in a high estimated permittivity value.…”
Section: Permittivity Estimation With Polarization Responsesupporting
confidence: 87%
See 1 more Smart Citation
“…The ratio values are calculated based on the angles (θ 1 , θ 2 ) corresponding to the maximum point inside the box. The estimated permittivity values of asphalt over the three zones, as indicated in Table 5, fall within the commonly encountered range for road asphalt [33][34][35] and are consistent with results reported in [27] over the same test circuit. The similar ε r 's of asphalt over the sand and air-gap zones are estimated from measurements acquired during the same sunny day, whereas over the geotextile zone, the measurement took place after a rain event, resulting in a high estimated permittivity value.…”
Section: Permittivity Estimation With Polarization Responsesupporting
confidence: 87%
“…The peak of the geotextile response is not located at the actual interface depth of 8 cm due to the slower propagation of electromagnetic waves in the host medium. By taking the dielectric permittivity of asphalt, ε r ≈ 5, as reported in [27], into account, the depth axis can be scaled by √ ε r , shifting back the response of the layer to approximately 20 cm. The profiles measured in the C and X bands exhibit a comparable ratio between the reflectivities of the ground surface and of the defect layer.…”
Section: Comparison Of Configurationsmentioning
confidence: 99%
“…However, the simulation results suggested that the PUMA algorithm can be further enhanced in the case of fully correlated echoes, and this can be done by extending the PUMA algorithm to directly exploit the properties of the rank-deficient source covariance matrix. In the near future, it is planned to test PUMA on the existing field database in [43].…”
Section: Discussionmentioning
confidence: 99%
“…Many standard tests empirically test the asphalt performance temporarily under controlled laboratory conditions that do not represent the real scenarios in the field [ 170 ]. Alternatively, accelerated pavement testing using Heavy Vehicle Simulator or Pavement Fatigue Carousel is currently being used to test the surface and structural changes of asphalt [ 171 , 172 ]. However, some parameters including gaseous emissions level when laying hot asphalt and the release of microplastics when plastic-modified roads are open to traffic due to abrasion exerted by vehicle tires cannot be assessed via accelerated pavement testing [ 164 ].…”
Section: Environmental and Human Health Adverse Effects Of Plastic Roadsmentioning
confidence: 99%